The Value Relevance of Intellectual Capital on Firm Performance in Transportation Industry - Olivia Idrus; Noorina Hartati (Journal of Economics, Business, and Government Challenges, 2020)
Previous studies that investigate the relationship between intellectual capital and financial performance or market value show different results. Meanwhile, intellectual capital begins to overtake physical assets as the most important assets for firms. It also happens in transportation industry. Transportation industry has a big influence on social and economic activities. Therefore, this study aims to analyze the effect of different measures of intellectual capital on firms’ performance. We use transportation firms listed in the Indonesian Stock Exchange (IDX) in 2011-2015. We use three independent variables in this study, namely, Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and Structural Capital Value Added (STVA) as the proxies of intellectual capital that are measured using the VAICTM model by Pulic (1998). The dependent variables are Return on Assets (ROA) and Return on Equity (ROE) as the proxies of firm performance. By using multivariate linear regression analysis, we show that VACA (CE), VAHU (HC) and STVA (SC) variables do not affect ROA and ROE as the proxies of firm performance. However, the VAIC TM variable that combines VACA (CE), VAHU (HC) and STVA (SC) positively affect both ROA and ROE.